EXTRACTION AND GCIMS ANALYSIS OF THE ESSENTIAL OIL OF OCIMUM BASILICUM (CaMaRa) (Biological Sciences - PJSIR, 2022)
A combination of GC ane!GC/MS has been used to characterise chemical composition or essential oil hydrodistilledfrom comoro variety of Ocimum basilicum grown in various parts of Pakistan. Among the forty four compoundsidentified, methyl chavicol (83.58-87.21 %), I, 8-cineol (2.45-3.37%), tinalool (0.04 - 2.69%) and methyl eugenol(1.4 - 2.68%), are predominantly present while other compounds particularly monoterpenes and sesquirerpencs hydrocarbonsare found only in traces. Variations in the essential oil composition ami yield during hydrodistillation are alsoreported.